Problems now and in the past - Emil Küng (Intereconomics, 1974)
In some places, voices are raised today which assert that development aid is not worth the noise that is being made about it, because the industrialised countries went through exactly the same phase of development by their own, unaided efforts and still had arrived where they are now. Any development aid, so it is said, will only paralyse the determination of LDCs to aid themselves. The author discusses this assertion in the following article.
Keywords: 330; Development Conditions